Conductivity and Dielectric Studies of Methylcellulose/Chitosan-NH4CF3SO3 Polymer Electrolyte - Hamdan, KZ; Khiar, ASA (Trans Tech Publications Ltd, 2024)
Films of methyl cellulose (MC) /chitosan blends were prepared via solution casting technique and their properties with different amount of ammonium trilate, NH4CF3SO3 were compared. Measurements of conductivity as a function of frequency at room temperature on these films were carried out using HIOKI 3532-50 LCR Hi-Tester where the frequency was set between 50 Hz to 1 MHz. Samples having 40 wt% of NH4CF3SO3 exhibit the highest room temperature conductivity of (4.99+4.18) x 10(-6) Scm(-1). Dielectric data were analyzed using complex permittivity and complex electrical modulus for the sample with the highest ionic conductivity.